Quality of concrete : one example in the north of Portugal - Cunha, P. J. (2010)
The non-quality and non-conformity of concrete, simulates the development of pathologies into the structure and consequently in coatings and masonry. So an early degradation of the buildings could be reached. The objectives of this study were he characterization of the procedures adopted for the production concrete n some works in the north of Portugal, determining he strength class required in the project. At this point, we performed the evaluation of the compressive resistance f concrete n situ and the comparison with the strength class obtained n the works under study. It was found that the quality of concrete in situ is higher than the obtained with standard samples. W can say that when more extensive, fast and tight s the inspection, better you can control and make the corrections in time, in order to maintain the quality of concrete used. It is important for a proper awareness, a training and formation of the persons involved in this matter.